PERLINDUNGAN HUKUM TERHADAP KORBAN PENJUALAN BARANG HASIL TINDAK PIDANA PENCURIAN DI KABUPATEN BULELENG - Kadek Gesa Ananda Jati Utama; Made Sugi Hartono; Dewa Bagus Sanjaya (Program Studi PPKn Jurusan Hukum dan Kewarganegaraan Undiksha Singaraja, 2022)
The purpose of this study is to (1) analyze the legal protection of victims of the sale of goods resulting from the crime of theft in Buleleng district. (2) find out what are the obstacles faced by the Buleleng Regency Police in providing legal protection to victims of the sale of goods resulting from the crime of theft in Buleleng Regency. This type of research is empirical legal research with a descriptive nature of research. The location of this research was conducted in Buleleng Regency. Data collection techniques used are document studies, observations and interviews. The technique of determining the subject used is a purposive sampling technique. Data processing and analysis techniques were carried out qualitatively. The results of the study indicate that legal protection for victims of the sale of goods resulting from the crime of theft in Buleleng Regency has not gone well. This is reflected in the fact that the status of the person buying the goods resulting from the crime of theft is uncertain, so that the legal protection provided is also less than optimal. The obstacle faced by the Buleleng District Police in providing legal protection to victims of the sale of goods resulting from the crime of theft in Buleleng Regency is the problem of the status of the buyer of the stolen goods being uncertain so that the protection provided is only a protection mechanism as a witness.